2012
DOI: 10.1186/1471-2474-13-229
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma vs hyaluronic acid to treat knee degenerative pathology: study design and preliminary results of a randomized controlled trial

Abstract: BackgroundPlatelet Rich Plasma (PRP), a blood-derived product rich in growth factors, is a promising treatment for cartilage defects but there is still a lack of clinical evidence. The aim of this study is to show, through a randomized double blind prospective trial, the efficacy of this procedure, by comparing PRP to Hyaluronic Acid (HA) injections for the treatment of knee chondropathy or osteoarthritis (OA).Methods109 patients (55 treated with HA and 54 with PRP) were treated and evaluated at 12 months of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
327
3
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(351 citation statements)
references
References 33 publications
13
327
3
8
Order By: Relevance
“…Nine RCTs were included in the results, 15,16,[21][22][23][33][34][35]38 3 of which were double blinded ( Table 2). Hyaluronic acid was used for the control groups in 7 RCTs, saline was used in 1 study, and an exercise program was used in another.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…Nine RCTs were included in the results, 15,16,[21][22][23][33][34][35]38 3 of which were double blinded ( Table 2). Hyaluronic acid was used for the control groups in 7 RCTs, saline was used in 1 study, and an exercise program was used in another.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…Of the three comparative studies included in this assessment, two used hyaluronic acid, an inappropriate comparator for the Australian setting. 21,22 No comparative studies were identified that compared the use of PRP to NSAIDs, the current treatment option for osteoarthritis of the knee in Australia.…”
Section: Resultsmentioning
confidence: 99%
“…84,85 These preclinical trials have led to a few small clinical studies. A 2012 review by Filardo et al 70 found 2 pre-clinical papers and 5 clinical trials focusing on the use of BMC in cartilage regeneration. Although these studies have small numbers, they offer a good start at unraveling the clinical potential of BMC.…”
Section: Autologous Bone Marrow Concentrate (Bmc)mentioning
confidence: 99%
“…However, middle-aged patients with moderate to severe OA demonstrated no significant benefit with PRP over HA. 45,70 Knop et al 71 conducted a comprehensive and systematic search of the literature on the use of PRP in the treatment of OA of the knee. A total of 23 studies were selected with nine being controlled trials and of these seven randomized, which included total of 725 patients.…”
mentioning
confidence: 99%